Studi Literatur: Pengaruh Whistleblowing Dan Bystander Effect Terhadap Fraud - Linda Novia Sari; Tri Ratnawati (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This study aims to confirm the effect of whistleblowing and bystander effect on fraud. Type of The type of research used by the author is a literature study. Data collection techniques This research data collection technique uses archival data collection techniques in the form of research results and research articles published .Data analysis method used by used by researchers is a descriptive qualitative approach through literature review. literature (literature review). The results of this study indicate that the effect of whistleblowing and bystander effect have a positive effect on fraud.